The Effect of Special Exercises On Power Defined By Speed Development Of Fencers' Legs - Altay, Usama; Mohammed, Alaa (Journal of Physical Education, 2019)
The aim of the research is to develop strength defined by speed of fencers' legs through special exercises. The researchers used the experimental method. One group of (6) advanced fencers from Iraq club were selected deliberately. The pretests were applied for strength defined by speed of fencers' legs followed by the training program. The training program consisted of (8) weeks with (3) training sessions per week using high intensity interval training (70 – 85%) to develop strength defined by speed. Posttests were conducted then the results were collected and treated using proper statistical operations. The researchers concluded that the proposed special exercises have great effect in developing strength defined by speed of fencers' legs.